PERSPECTIVE - Steno, Targioni and the two forerunners - Dominici, Stefano (Journal of Mediterranean Earth Sciences, 2014)
The brief and enigmatic Forerunner written by Nicholas Steno after a two-year residence in Tuscany (1667- 1668) contains several basic intuitions of earth sciences. His work influenced contemporary natural philosophers through Europe, but was seemingly forgotten in the course of the next century. Only in Florence the naturalist and polymath Giovanni Targioni Tozzetti undertook a geological study of Tuscany and tested the validity of Steno’s hypothesis on the origin of mountains and hills. In relevant passages of his Travels (1751-1754), Targioni expressed a substantial agreement with Steno’s reconstruction, therefore planning a modernized version of Steno’s theory of the earth, which he published in his own Forerunner (1754). In this work he sets the agenda for the new disciplines of physical chorography and topography, wishing to complete their application to Tuscany in his own lifetime, so that Tuscany could be presented as a template of the earth. His fame as author of Travels and owner of one of the best natural history museums of Europe reached many savants who visited him and learned the results of his fieldwork and his geotheory. Some of the people who met with Targioni have influenced the development of geology, and important aspects of his ideas can be found in their writings. For example, the two sets of strata of Steno’s Forerunner were retained in Targioni’s scheme, in their turn representing the basic distinction of Secondary and Tertiary strata first brought to international attention by Giovanni Arduino. Targioni conceived the need for a methodological change in the study of the earth and its history, praising fieldwork and mapping. He inspired Nicolas Desmarest, a pioneer of modern geology who travelled Tuscany testing Targioni’s hypotheses and learned about his understanding of Steno’s geology. Neither Steno nor Targioni could develop their particular vision of the history of the earth were it not for the exceptional variety of rocks of Tuscany, the abundant Tertiary fossils and the clear angular unconformity between Secondary and Tertiary strata. Giambattista Brocchi, among the most influential geologists of the early nineteenth century, travelled Tuscany on the footsteps of Targioni, validating his vision of the basic stratigraphy and bringing the concept of Tertiary fossils and strata to a wider public. Brocchi refocused attention on Tuscany, and key figures of the history of geology like Alexandre Brongniart and Charles Lyell duly came to see with their own eyes. In Brocchi’s Subapennine fossil conchology the link between Steno and Targioni was lost track of, but Steno’s work on the organic origin of fossils was brought to the general attention after almost one century of near oblivion. At the same time, Brocchi was unconsciously revaluating Steno’s history of the earth.